Male and female WorldSID and post mortem human subject responses in full-scale vehicle tests. (29th May 2017) - Yoganandan, Narayan; Humm, John; Pintar, Frank; Rhule, Heather; Moorhouse, Kevin; Suntay, Brian; Stricklin, Jim; Rudd, Rodney; Craig, Matthew
ABSTRACT: Objective : This study compares the responses of male and female WorldSID dummies with post mortem human subject (PMHS) responses in full-scale vehicle tests. Methods: Tests were conducted according to the FMVSS-214 protocols and using the U.S. Side Impact New Car Assessment Program change in velocity to match PMHS experiments, published earlier. Moving deformable barrier (MDB) tests were conducted with the male and female surrogates in the left front and left rear seats. Pole tests were performed with the male surrogate in the left front seat. Three-point belt restraints were used. Sedan-type vehicles were used from the same manufacturer with side airbags. The PMHS head was instrumented with a pyramid-shaped nine-axis accelerometer package, with angular velocity transducers on the head. Accelerometers and angular velocity transducers were secured to T1, T6, and T12 spinous processes and sacrum. Three chest bands were secured around the upper, middle, and lower thoraces. Dummy instrumentation included five infrared telescoping rods for assessment of chest compression (IR-TRACC) and a chest band at the first abdomen rib, head angular velocity transducer, and head, T1, T4, T12, and pelvis accelerometers. Results : Morphological responses of the kinematics of the head, thoracic spine, and pelvis matched in both surrogates for each pair. The peak magnitudes of the torso accelerations were lower for the dummy than for the biological surrogate. The brain rotational injury criterion (BrIC) response was the highest in the male dummy for the MDB test and PMHS. The probability of AIS3+ injuries, based on the head injury criterion, ranged from 3% to 13% for the PMHS and from 3% to 21% for the dummy from all tests. The BrIC-based metrics ranged from 0 to 21% for the biological and 0 to 48% for the dummy surrogates. The deflection profiles from the IR-TRACC sensors were unimodal. The maximum deflections from the chest band placed on the first abdominal rib were 31.7 mm and 25.4 mm for the male and female dummies in the MDB test, and 37.4 mm for the male dummy in the pole test. The maximum deflections computed from the chest band contours at a gauge equivalent to the IR-TRACC location were 25.9 mm and 14.8 mm for the male and female dummies in the MDB test, and 37.4 mm for the male dummy in the pole test. Other data (static vehicle deformation profiles, accelerations histories of different body regions, and chest band contours for the dummy and PMHS) are given in the appendix. Conclusions : This is the first study to compare the responses of PMHS and male and female dummies in MDB and pole tests, done using the same recent model year vehicles with side airbag and head curtain restraints. The differences between the dummy and PMHS torso accelerations suggest the need for design improvements in the WorldSID dummy. The translation-based metrics suggest low probability of head injury. As the dummy internal sensor underrecorded the peak deflection, multipoint displacement measures are therefore needed for a more accurate quantification of deflection to improve the safety assessment of occupants.